A review of energy optimization modelling tools for the decarbonisation of wastewater treatment plants. (10th January 2021) - Nakkasunchi, Shalini; Hewitt, Neil J.; Zoppi, Claudia; Brandoni, Caterina
Abstract: Wastewater treatment plants strongly contribute to the Greenhouse Gas emissions of the water industry and are responsible for the 3% of the global energy demand. This proportion of energy is expected to double in the coming decade. It is therefore important to correctly investigate the optimal use of energy in wastewater treatment facilities that can reduce their Greenhouse Gas emissions. A review was developed on modelling tools that can be used for the analysis of the water-energy nexus in wastewater facilities, from over 200 research articles collected from different scientific resources published in the last 15 years. The aim was to analyse the state of art of existing tools to provide an aid for researchers and professionals to identify the most suitable tool to investigate decarbonisation strategies for wastewater facilities. Studies were grouped on the basis of the main intervention analysed: i) reduction of energy demand, ii) energy production from wastewater and iii) integration of the available renewable sources on-site (e.g. PV, hydro). The work developed also provides an overview of the most applicable decarbonisation strategies and their potential to reduce the CO2 emissions of wastewater facilities. Results show that identifying the best tool strongly depends on the main aim of the intervention. Existing tools, in fact, can help to analyse separately either technologies to reduce the energy demand or the integration of the most common renewable sources from both wastewater (i.e. biogas and heat recover) and renewable sources exploitable on site. However, the full decarbonisation of wastewater facilities can only happen by integrating different energy savings and renewables solutions. There is, therefore, the need for a comprehensive energy-water optimization tool able to understand how key water parameters influence the energy demand and to identify, on a single platform, the best energy saving solutions and the benefits coming from integrating different renewable sources. Such platform could help in enhancing the benefits of combined solutions, helping to maximise the reuse of the renewable energy produced onsite and any opportunity of energy savings. Graphical abstract: Image 1 Highlights: Wastewater treatment plants account for 56% greenhouse gas emissions of the water industry. An overview of potential energy decarbonisation strategies is presented. Analysis of energy optimization tools for wastewater treatment plants is developed. Modelling tools for assessing either the energy benchmarking or renewables are available. Need to integrate energy benchmarking, resource recovery and renewables in a single platform.